2014
DOI: 10.1353/cpr.2014.0012
|View full text |Cite
|
Sign up to set email alerts
|

Brentwood Community Health Care Assessment

Abstract: Background-The Community Alliance for Research Empowering Social Change (CARES) is an academic-community research partnership designed to train community members on research methods and develop the infrastructure for community-based participatory research (CBPR) to examine and address racial/ethnic health disparities. The Brentwood Community Health Assessment (BCHA) was developed through a CBPR pilot project grant from CARES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…A total of 50 community members were selected to participate in the first cohort of this 15-week-long research training program that is based on the Community Alliance for Research Empowering Social Change training (Coats et al, 2015; Goodman, Dias, & Stafford, 2010; Goodman et al, 2014; Goodman, Si, Stafford, Obasohan, & Mchunguzi, 2012). The Institutional Review Board at Washington University School of Medicine designated CRFT research as nonhuman subjects research.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 50 community members were selected to participate in the first cohort of this 15-week-long research training program that is based on the Community Alliance for Research Empowering Social Change training (Coats et al, 2015; Goodman, Dias, & Stafford, 2010; Goodman et al, 2014; Goodman, Si, Stafford, Obasohan, & Mchunguzi, 2012). The Institutional Review Board at Washington University School of Medicine designated CRFT research as nonhuman subjects research.…”
Section: Methodsmentioning
confidence: 99%
“…(Goodman, Johnson Dias, & Stafford, 2010). The CARES training was tailored to be region specific and culturally competent for the strengths and challenges in the Long Island community; results indicated that the training was successful, useful, and impactful (Goodman et al, 2010; Goodman, Si, Stafford, Obasohan, & Mchunguzi, 2012; Goodman et al, 2014). …”
mentioning
confidence: 99%
“…For instance, focus groups can be co-designed, co-facilitated, and collaboratively analyzed by community co-investigators (see for example, Johnson & Martínez Guzmán, 2013;McElfish et al, 2016). Other research partnerships have collaboratively developed and administered surveys as part of a community needs assessment (e.g., Goodman et al, 2014) or worked with community coresearchers to develop questions and conduct qualitative interviews (Watson & Marciano, 2015). The distinguishing feature of participatory research is stakeholder power in decision making and implementation; therefore, any research method or tool can be participatory if chosen and/or utilized collaboratively between academic and community partners.…”
Section: Participatory Research Methodsmentioning
confidence: 99%